PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFEKTIVITAS STRATEGI PEMASARAN DIGITAL PADA STARTUP LOKAL - Nayla Tri Audina; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The background of this study lies in the rapid growth of digital marketing, which requires local startups to manage information effectively in order to remain competitive. Many startups face limitations in capital, human resources, and data analysis capabilities, resulting in digital marketing strategies that are often suboptimal. This study aims to explain the role of Management Information Systems (MIS) in enhancing the effectiveness of digital marketing strategies among local startups. The method used is a literature review and conceptual analysis based on journals, books, and industry reports related to MIS and digital marketing. The results show that MIS plays a significant role in data integration, consumer analysis, campaign personalization, and real-time performance measurement. MIS helps startups optimize budgets, improve decision-making accuracy, and strengthen customer relationships through data-driven strategies. In conclusion, the implementation of MIS is a strategic necessity for local startups to improve digital marketing effectiveness, expand market reach, and support sustainable business growth.